Ocular Delivery of Atenolol Loaded Microsponge in-situ Gel: Development, Characterization and in-vitro Evaluation - Dhyani, Archana; Kumar, Ganesh (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim/Background: The purpose of the study was to fabricate and evaluate atenolol loaded micro-sponge in-situ gel. Materials and Methods: Oil in Oil Emulsion Solvent Diffusion Technique was used for formulation of microsponges by using different levels of polymers such as Eudragit RS-100 and Ethyl Cellulose. The prepared micro-sponges were evaluated for optical microscopy, percentage yield, drug content, entrapment efficiency and surface morphology studies. The micro sponges were loaded into in-situ gel. The gel was characterized for pH, rheological behavior, in vitro gelling capacity and in vitro drug release study. Results: The smicrosponges were found in the size range of 7.43 to 9.26μm. The formulation F1 has smallest particle size while F9 has largest size. The product yield varies from 66.98% to 89.87 %.The drug content was found to be maximum for formulation F8 which is 94.19%. Similarly, the entrapment efficiency was found maximum for formulation F8 which is 93.89%. The gel was characterized for pH. The pH of drug loaded microsponge gel were found in range of 7.43±0.27 to 9.26±0.61.Similarly, viscosity ranges from 32 to 39 cps. The data of in-vitro release shows that 60.12% drug was released up to 24hr. Conclusion: The mirosponges laden in situ gel was effectively prepared by oil in oil emulsion solvent diffusion method (O/O ESDM). Further, the formulation will provide benefits in terms of sustained/controlled release, reduces dosing frequency and provides better compliance to the patient.
Keywords: Microsponge; Atenolol; Ethyl Cellulose; Eudragit RS-100; in situ gel